Lower thermospheric‐enhanced sodium layers observed at low latitude and possible formation: Case studies. Issue 5 (9th May 2013) - Xue, X. H.; Dou, X. K.; Lei, J.; Chen, J. S.; Ding, Z. H.; Li, T.; Gao, Q.; Tang, W. W.; Cheng, X. W.; Wei, K.
Abstract : [1] We report two lower thermospheric‐enhanced sodium layer (TeSL) cases observed at a low‐latitude station, Lijiang, China (26.7°N, 100.0°E), on 10 March and 10 April 2012, respectively. The TeSLs in the two cases were located at altitudes near 122 and 112 km, respectively. In addition, strong sporadic sodium layers (SSLs) near 100 km accompanied the TeSL observed on 10 March 2012. Both the TeSLs and SSLs exhibited tidal‐induced downward motion. The adjacent ground‐based and space‐borne ionospheric radio observations showed strong E s layers before the appearance of the TeSLs, suggesting an " E s – TeSLs (SSLs)" chain formed through the tidal wind shear mechanism. Assuming that the vertical tidal wavelengths remain unchanged, it is found that in different regions caused by the tidal wind shear, different TeSLs evolution processes are expected: (1) in a tidal‐convergence region, a TeSL/SSL with a downward propagation phase is enhanced due to a rapid decrease in the Na + lifetime at the lower altitude; (2) in an ion convergence‐divergence interface region, a TeSL/SSL will still follow the tidal downward phase progression, but sodium density does not exhibit evident enhancement; and (3) when a TeSL/SSL enters into a tidal wind‐divergence zone, the layer density tends to decrease. Key Points: Two TeSLs events were observed at a low latitude region Radio observations suggest TeSLs/SSLs might be formed through the same mechanism Different ion vertical motion region indicates different TeSL evolution process